Doing evidence-based medicine? How NHS managers ration high-cost drugs. (August 2019) - Hughes, David; Doheny, Shane
Highlights: Funding high-cost drugs depends on a pragmatic, time-limited review of evidence. For funding to be approved both efficacy and exceptionality must be found. Tensions arise when efficacy but not exceptionality is present. Decision rules change over time due to political intervention and judicial review. Moral concerns about the value of a few extra months of life may affect decisions.